2001
DOI: 10.1182/blood.v97.4.1147
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the NMMHC-A gene cause autosomal dominant macrothrombocytopenia with leukocyte inclusions (May-Hegglin anomaly/Sebastian syndrome)

Abstract: Macrothrombocytopenia with leukocyte inclusions is a rare autosomal dominant platelet disorder characterized by a triad of giant platelets, thrombocytopenia, and characteristic Döhle body-like leukocyte inclusions. A previous study mapped a locus for the disease on chromosome 22q12.3-q13.2 by genome-wide linkage analysis. In addition, the complete DNA sequence of human chromosome 22 allowed a positional candidate approach, and results here indicate that the gene encoding nonmuscle myosin heavy chain-A, NMMHC-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
112
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 21 publications
12
112
0
1
Order By: Relevance
“…1,2 We previously showed diffuse NMMHC-IIA distribution in lymphocytes from patients with MYH9 disorders. 5,11 We found that both wild-type and mutant NMMHC-IIA were diffusely distributed in the lymphocyte cytoplasm ( Figure 3B). Although the original report of MayHegglin anomaly described that inclusion bodies are absent in monocytes, this remains controversial.…”
Section: Mutant Nmmhc-iia Polypeptide Is Diffusely Distributed In Lymmentioning
confidence: 92%
See 2 more Smart Citations
“…1,2 We previously showed diffuse NMMHC-IIA distribution in lymphocytes from patients with MYH9 disorders. 5,11 We found that both wild-type and mutant NMMHC-IIA were diffusely distributed in the lymphocyte cytoplasm ( Figure 3B). Although the original report of MayHegglin anomaly described that inclusion bodies are absent in monocytes, this remains controversial.…”
Section: Mutant Nmmhc-iia Polypeptide Is Diffusely Distributed In Lymmentioning
confidence: 92%
“…NMMHC-IIA is homogeneously distributed in the cytoplasm of normal resting platelets. 5,11,20,21 PRB440P diffusely stained the cytoplasm of platelets from the patients, and intensely stained the cell periphery ( Figure 3A,B left panels). In contrast, most platelets were negative for NT629 staining ( Figure 3A,B right panels) and only those that were similar to or larger than erythrocytes (ϳ 10% of total platelets) were weakly stained in the cytoplasm but not in the cell periphery ( Figure 3D).…”
Section: Mutant Nmmhc-iia Polypeptide Is Uniformly Distributed At Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of this disorder was totally unknown until recently, when the disease locus was mapped to chromosome 22q12.3-q13.2 by linkage analysis [10,11]. The gene responsible for the disorder was then identified by a positional candidate gene approach as MYH9, which encodes a large cytoplasmic protein (NMMHC-IIA) [12][13][14]. NMMHC-IIA is expressed in many different tissues, including platelets, leukocytes, kidney, and cochlea and is involved in cell motility, cytokinesis, cell polarity, and cell architecture.…”
Section: Elucidation Of Genetic Basismentioning
confidence: 99%
“…However, a surveillance strategy with regular blood counts may identify patients in an earlier stage of the leukemia, thus reducing the risk for bleeding and infectious complications and increase cure rates. Therefore, we suggest a stepwise diagnostic algorithm in which the most frequent causes of hereditary thrombocytopenia (e.g., MayHegglin anomaly and Fechtner syndrome [13][14][15][16]) are excluded by clinical investigations and subsequently AML1 mutational analyses are performed. Fig.…”
mentioning
confidence: 99%